The impact of local content requirements on the development of export competitiveness in solar and wind technologies. (October 2022) - Scheifele, F.; Bräuning, M.; Probst, B.
Abstract: Governments across the globe are implementing targeted industrial policies to reap the socio-economic benefits of renewable power deployment for their local industries. Here, we analyse local content requirements, a specific type of industrial policy that incentivizes local manufacturing through requiring minimum shares of locally produced inputs in renewable energy projects. Local content requirements are one of the most prominent industrial policy tools, with more than 140 applications across different sectors since 2008, yet their impact on industrial development is not well established. We create a panel dataset from 1995 to 2017 of 124 countries, among which 17 introduced local content requirements in wind and solar PV, to analyze the policies' impact on exports. We employ synthetic control methods to create country-specific counterfactuals. For most countries, local content requirements have not led to a significant increase in exports of solar and wind energy components. The exceptions are China and Spain, which built significant export capacities in wind energy. A central reason for the limited impact of local content requirements is likely that countries target wind and solar components that are too far away from their existing industrial structures. We show that countries that have succeeded in breaking into solar or wind exports have already exhibited export capabilities in related industries before the introduction of local content requirements, such as electronics for solar PV. Policymakers should carefully consider the potential of existing industrial structures before introducing local content requirements. Highlights: Countries that introduced local content requirements have not developed competitive export sectors in solar and wind energy components, except for China and Spain. Solar and wind energy technology exhibit high average complexity levels and the distance to current complexity levels of developing countries may explain their difficulties to develop competitive manufacturing in these sectors. Large heterogeneities in product complexity at the component level offer diversification opportunities for economies with less technological capabilities. Previous capacities in related industries, such as electronics in the case of solar PV or steel and machinery in wind energy are important for successful diversification.